Metabolic Plasticity of Tumor Cell Mitochondria - Cannino, Giuseppe; Ciscato, Francesco; Masgras, Ionica; Sánchez-Martín, Carlos; Rasola, Andrea (Frontiers in Oncology, 2018)
Mitochondria are dynamic organelles that exchange a multiplicity of signals with other cell compartments, in order to finely adjust key biological routines to the fluctuating metabolic needs of the cell. During neoplastic transformation, cells must provide an adequate supply of the anabolic building blocks required to meet a relentless proliferation pressure. This can occur in conditions of inconstant blood perfusion leading to variations in oxygen and nutrient levels. Mitochondria afford the bioenergetic plasticity that allows tumor cells to adapt and thrive in this ever changing and often unfavourable environment. Here we analyse how mitochondria orchestrate the profound metabolic rewiring required for neoplastic growth.